Electronegative zeolite-like metal sulfide composite material as well as preparation method and photocatalytic hydrogen production application thereof

The negatively charged zeolite-type metal sulfide composite material prepared through cation exchange and post-treatment reactions solves the problems of complex preparation of porous materials and low atomic utilization, and achieves efficient and stable photocatalytic hydrogen production performance.

CN119857500APending Publication Date: 2025-04-22FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411783587.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the existing field of photocatalytic hydrogen production, the preparation of porous material host and guest systems is complex and the atomic utilization rate is low, resulting in insufficient catalytic activity and stability.

Method used

By cation exchange reaction and post-treatment reaction of negatively charged zeolite-type metal sulfide materials, a composite material with nanoparticles anchored to the zeolite-type metal sulfide frame was obtained, which simplified the preparation process and improved the atomic utilization rate.

Benefits of technology

The composite material exhibits efficient and stable performance in photocatalytic hydrogen production, overcomes the problem of easy agglomeration and shedding of nanoparticles in the original materials, and significantly improves photocatalytic activity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857500A_ABST
    Figure CN119857500A_ABST
Patent Text Reader

Abstract

The invention discloses an electronegative zeolite-like metal sulfide composite material as well as a preparation method and photocatalytic hydrogen production application thereof, and belongs to the technical field of photocatalysis. According to the technical scheme, the preparation method comprises the following steps: carrying out cation exchange reaction on an electronegative zeolite-like metal sulfide material to obtain a material modified by different cations, and carrying out post-treatment reaction to obtain a composite material with nanoparticles anchored on a zeolite-like metal sulfide framework; the nanoparticles in the composite material are uniformly and stably anchored on the electronegative zeolite-like metal sulfide, the tight combination of the nanoparticles and the host has chemical binding and stabilizing effects, and the stability of the nanoparticles is enhanced to the greatest extent. The composite material shows huge application potential in the field of photocatalytic hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an electronegative zeolite-type metal sulfide composite material, a preparation method thereof, and a photocatalytic hydrogen production application thereof, and belongs to the field of photocatalytic technology. Background Art

[0002] With the increase in resource consumption and the depletion of fossil fuels, energy crisis and environmental pollution have become major problems facing mankind. Hydrogen energy, as a clean and efficient energy source, is of great significance to promoting energy structure transformation and responding to climate change (Nat. Photonics 2012, 6, 511-518; Nature 1972, 238, 37-38). At present, the main hydrogen production technologies include fossil energy reforming hydrogen production, industrial by-product gas hydrogen production, water electrolysis hydrogen production, biomass direct hydrogen production and solar photocatalytic water decomposition hydrogen production (photocatalytic hydrogen evolution from water splitting; PHE). Among them, solar PHE has attracted much attention because it efficiently converts solar energy into hydrogen energy in a green and renewable way (ACS Catal. 2019, 9, 345-364).

[0003] One of the keys to improving the efficiency of solar PHE lies in the development of efficient semiconductor PHE. In addition to meeting the requirement of an energy band spanning the redox potential of water, an ideal semiconductor PHE catalyst also needs to have the characteristics of absorbing a wide solar spectrum, high electron-hole separation efficiency, and rapid surface catalytic reaction (Chem. Soc. Rev. 2014, 43, 7787-7812; Chem. Soc. Rev. 2019, 48, 2109-2125). However, designing and preparing semiconductor PHE catalysts with the above characteristics at the same time is a huge challenge. In particular, during the photocatalytic process, photogenerated electrons and holes often recombine in the nanosecond range, which seriously restricts the electron-hole separation efficiency of the catalyst and leads to lower PHE activity (Angew. Chem. Int. Ed. 2022, 61, e202117567). As mentioned above, one of the main bottlenecks of photocatalytic hydrogen production is to overcome this spontaneous electron-hole pair recombination. The simplest solution is to increase the speed of carrier migration. Encapsulating other functional materials (precious metals, dyes or other catalytically active substances) in porous materials to prepare host-guest system composites is one of the effective ways to improve photocatalytic activity (Angew.Chem.2005,117,5433-5437). Compared with single-component systems, these functional materials can be used as photosensitizers, charge transfer media, and catalytic active centers to make composite materials show enhanced or even novel performance (J.Am.Chem.Soc.2022,144,22747-22758). However, the preparation method of such materials is complicated and nanoparticles are easily agglomerated and fall off, resulting in low atomic utilization, which limits its final application (Chin.J.Catal.2022,43,2332-2341). Therefore, it is urgent to prepare a stable, simple synthesis method and high atomic utilization composite material. Summary of the invention

[0004] In order to solve the problems of complex preparation of host-guest systems of porous materials and low atomic utilization in the current field of photocatalytic hydrogen production, the present application has developed a technical solution for a class of negatively charged zeolite-type metal sulfide-based composite materials with simple preparation and high atomic utilization, wherein the negatively charged zeolite-type metal sulfide material is subjected to a cation exchange reaction to obtain materials modified with different cations, and then a post-treatment reaction is performed to obtain a composite material in which nanoparticles are anchored in the framework of the zeolite-type metal sulfide.

[0005] This application adopts the following technical solutions:

[0006] According to the first aspect of the present application, a method for preparing a negatively charged zeolite-type metal sulfide composite material is provided, comprising the following steps:

[0007] S1, placing a mixture containing a metal salt, sulfur powder, a cation source, and water in a sealed container, and performing a hydrothermal reaction to obtain a negatively charged zeolite-type metal sulfide precursor;

[0008] S2, subjecting a mixture containing a negatively charged zeolite-type metal sulfide precursor, a metal cation source, and water to a metal cation exchange reaction to obtain a metal cation-modified negatively charged zeolite-type metal sulfide;

[0009] S3, post-treating the negatively charged zeolite-type metal sulfide modified with metal cations and a post-treating agent in a solvent to obtain the negatively charged zeolite-type metal sulfide composite material.

[0010] Optionally, in step S1, the metal element in the metal salt is selected from at least one of In, Ga, and Ge.

[0011] Optionally, when there are two metal salts, the metal element is selected from one of the combinations of In / M (M = Zn, Cd, Fe, Co, Mn, Ge, Sn, Cu), Ga / Ge, Ga / Sn, Ge / Zn, Ge / Cu, Ge / Mn, Sn / Zn, and Sn / Cd.

[0012] Optionally, when there are three metal salts, the metal element is selected from one of the combinations of Ge / Cd / Zn, Ge / Ga / Zn, Ge / Sn / Zn, Zn / Ga / Ge, Cu / Ga / Sn, Cu / In / Sn, Mn / Ga / Sn, and Mn / Zn / In.

[0013] The anions in the metal salts in the present application are not strictly limited, and those skilled in the art can select them according to their needs.

[0014] Optionally, in step S1, in step S1, the cation source in the cation source is selected from at least one of cesium salts, rubidium salts, strontium salts, potassium salts, sodium salts, amine salts, methylamine, dimethylamine, tris(2-aminoethyl)amine, N-aminoethylpiperazine, N-(2-aminoethyl)morpholine, and 1-butyl-3-methylimidazole.

[0015] Optionally, in step S1, the cation source is selected from at least one chloride of the above cations.

[0016] Optionally, in step S1, the molar ratio of the metal salt to the sulfur powder and the cation source is 1:(1-5):(5-20) based on the molar amount of the elements.

[0017] Optionally, in step S1, the usage ratio of the cation source to water is 1 mmol: 1-30 mL.

[0018] Optionally, in step S1, the conditions of the hydrothermal reaction include: a reaction temperature of 100 to 220° C., a reaction time of 24 to 240 h, and natural cooling after the reaction is completed.

[0019] Optionally, in step S2, the cation in the metal cation source is selected from Cd 2+ 、Zn 2+ , Pb 2+ 、Mo 4+ , Cu 2+ 、Bi 3+ 、Ag + 、Co 2+ 、Ni 2+ , Fe 2+ At least one of .

[0020] Optionally, the metal cation source is selected from at least one of acetate metal salts, nitrate metal salts, oxalate metal salts, chloride metal salts, and carbonate metal salts of the above cations.

[0021] Optionally, the solvent in step S2 is one of water, ethanol and N-methylpyrrolidone.

[0022] Optionally, in step S2, the cation concentration in the metal cation source is 0.05 to 0.5 mol / L.

[0023] Optionally, in step S2, the weight ratio of the negatively charged zeolite-type metal sulfide precursor to the metal cation source is 1:0.5-3.

[0024] Optionally, in step S2, the weight ratio of the negatively charged zeolite-type metal sulfide precursor to the metal cation source is 1:0.5-3.

[0025] Optionally, the weight ratio of the negatively charged zeolite-type metal sulfide precursor to the post-treatment agent in step S3 is 1:1-10.

[0026] Optionally, the ratio of the negatively charged zeolite-type metal sulfide precursor to the solvent in step S3 is 1 mg: 0.005-0.1 mL.

[0027] Optionally, in step S2, the conditions for the metal cation exchange reaction include: being carried out under at least one of stirring and shaking, the reaction temperature is 20 to 120° C., and the reaction time is 12 to 72 hours.

[0028] Optionally, in step S2, the stirring and / or shaking speed is 200-1000 rpm.

[0029] Optionally, in step S3, the post-treatment reaction is selected from one of a sulfurization reaction, a halogenation reaction, and a phosphating reaction.

[0030] Optionally, the solvent in step S3 is one of water, ethanol and N-methylpyrrolidone.

[0031] Optionally, when the post-treatment reaction is a sulfidation reaction, the cation in the metal cation source is selected from Cd 2+ 、Zn 2+ , Pb 2+ 、Mo 4+ , Cu 2+ 、Bi 3+ One of the above, the post-treatment agent is a sulfur source.

[0032] Optionally, the sulfur source is selected from at least one of sodium sulfide, thiourea and thioacetamide.

[0033] Optionally, the conditions for the vulcanization reaction include: reacting under at least one of stirring, shaking, and hydrothermal conditions, and the vulcanization reaction time is 6 to 24 hours.

[0034] Optionally, when the vulcanization reaction is carried out under stirring and / or shaking conditions, the temperature of the vulcanization reaction is 20-100° C., and the stirring and / or shaking speed is 200-1000 rpm.

[0035] Optionally, when the vulcanization reaction is carried out under hydrothermal conditions, the temperature of the vulcanization reaction is 100-200°C.

[0036] Optionally, when the post-treatment reaction is a halogenation reaction, the cation in the metal cation source is Ag. + , the post-treatment agent is a halogen source.

[0037] Optionally, the halogen source is selected from at least one of potassium halide and sodium halide.

[0038] Optionally, the halogen in the halogen source is selected from at least one of chlorine, bromine and iodine.

[0039] Optionally, the halogenation reaction conditions include: dark stirring and / or dark shaking at a speed of 200 to 1000 rpm, the halogenation reaction temperature is 20 to 40° C., and the halogenation reaction time is 0.5 to 6 h.

[0040] Optionally, when the post-treatment reaction is a phosphating reaction, the cation in the metal cation source is selected from Co 2+ 、Ni 2+ , Fe 2+ One of the post-treatment agents is a phosphorus source.

[0041] Optionally, the phosphorus source is selected from at least one of phosphine and sodium hypophosphite.

[0042] Optionally, the conditions of the phosphating reaction include: in an inactive atmosphere, the phosphating reaction temperature is 300-600° C., and the phosphating reaction time is 2-6 hours.

[0043] Optionally, the non-reactive atmosphere is selected from an inert atmosphere.

[0044] Optionally, the inert atmosphere is selected from at least one of nitrogen and argon.

[0045] The core of the technical solution of the present application is to obtain materials modified with different cations by metal cation exchange reaction of negatively charged zeolite-type metal sulfide, and then obtain a composite material in which nanoparticles are anchored on the framework of zeolite-type metal sulfide through various post-treatment reactions. The close combination of nanoparticles and the host has a chemical binding and stabilizing effect, which maximizes the stability of the nanoparticles. The main material of the composite material is negatively charged zeolite-type metal sulfide, and the guest nanoparticle is one of metal sulfide, metal halide, and metal phosphide.

[0046] According to another aspect of the present application, a negatively charged zeolite-type metal sulfide composite material prepared by the above-mentioned preparation method is provided, wherein the negatively charged zeolite-type metal sulfide composite material comprises a host material and guest nanoparticles;

[0047] The main material is an electronegative zeolite-type metal sulfide;

[0048] The guest nanoparticles are selected from at least one of sulfides, halides, and phosphides of cations in the metal cation source;

[0049] The guest nanoparticles are anchored to the host material.

[0050] According to another aspect of the present application, there is also provided a negatively charged zeolite-type metal sulfide composite material prepared by the above preparation method or the use of the above negatively charged zeolite-type metal sulfide composite material as a catalyst in photocatalytic hydrogen production.

[0051] The beneficial effects of this application include:

[0052] (1) The preparation method of the negatively charged zeolite-type metal sulfide composite material provided in the present application anchors the guest nanoparticles on the zeolite-type metal sulfide framework so that the guest nanoparticles are uniformly dispersed and anchored on the host, thereby significantly improving the atomic utilization rate while ensuring the stability of its photocatalytic performance, thereby overcoming the problem that "the guest nanoparticles in the composite material in the prior art are easy to aggregate and leach, resulting in a decrease in its utilization rate".

[0053] (2) The preparation method adopted in the present application is to subject the negatively charged zeolite-type metal sulfide material to a cation exchange reaction, and after a simple post-treatment, a composite material in which nanoparticles are anchored on the negatively charged zeolite-type metal sulfide framework can be obtained, which simplifies the preparation process and saves costs. In addition, by changing the type of exchanged metal cations and adjusting the post-treatment method, the type of guest material can be controllably adjusted to obtain a variety of composite photocatalytic materials.

[0054] (3) The negatively charged zeolite-type metal sulfide composite material provided in the present application plays an important role in the field of photocatalysis: the close combination of the guest nanoparticles and the host has a chemical binding and stabilizing effect, which can accelerate the electron-hole separation and charge transfer between the host and the guest, ensuring that the photocatalytic reaction is long-lasting and efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 The PXRD of the electronegative zeolite-type metal sulfide 1* obtained in Test Example 1 of the present application;

[0056] Figure 2 The PXRD of the negatively charged zeolite-type metal sulfide composite material A1# obtained in Test Example 1 of the present application;

[0057] Figure 3 This is the scanning electron microscope image of A1# obtained in Test Example 1 of this application;

[0058] Figure 4 This is the transmission electron microscope image of A1# obtained in Test Example 1 of this application;

[0059] Figure 5 Performance diagram of photocatalytic hydrogen production of 1* and A1# for 8 hours obtained in Test Example 1 of this application;

[0060] Figure 6 This is a bar graph of photocatalytic hydrogen production of 1* and A1# for 8 hours obtained in Test Example 1 of this application;

[0061] Figure 7 This is the performance diagram of photocatalytic hydrogen production of A1# for 60 hours obtained in Test Example 1 of this application;

[0062] Figure 8 This is the PXRD of A1# obtained in Test Example 1 of this application after 60 hours of photocatalytic hydrogen production. DETAILED DESCRIPTION

[0063] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0064] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0065] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0066] In this embodiment, the powder X-ray diffractometer is a MiniFlex II instrument, and the specific parameters are CuKα radiation, 30 kV, 15 mA,

[0067] The scanning electron microscope was a JEOL JSM-6700F model.

[0068] The transmission electron microscope was tested using JEOL JEM-2100 model.

[0069] The photocatalytic performance was tested using the Beijing Zhongjiao Jinyuan CEL-SPH2N automatic online photocatalytic water decomposition and hydrogen production test system, with methanol as the sacrificial reagent.

[0070] Example 1

[0071] (1) 0.0752 g (0.25 mmol) of In(NO3)3·xH2O, 0.0321 g (1 mmol) of sulfur powder and 1 mL of 33% dimethylamine aqueous solution were weighed and placed in a 20 mL polytetrafluoroethylene liner, stirred and mixed evenly, and then placed in a stainless steel reactor, heated in an oven at 160°C for 5 days, taken out and naturally cooled at room temperature, and washed repeatedly with industrial ethanol and water to obtain a negatively charged zeolite-type metal sulfide 1*;

[0072] (2) 250 mg of negatively charged zeolite-type metal sulfide 1* was placed in a glass bottle, 125 mg of cadmium acetate dihydrate, 20 mg of nickel acetate dihydrate and 7.5 mL of deionized water were added to the glass bottle, and the mixture was stirred at room temperature for 72 h for metal cation exchange reaction at a rotation speed of 600 rpm. After multiple washings, a metal cation-modified zeolite-type metal sulfide 1# was obtained;

[0073] (3) The metal cation modified zeolite-type metal sulfide 1# was redispersed in 7.5 mL of deionized water, 0.77 g of Na2S·9H2O was added, and the mixture was stirred at room temperature for 72 h for post-treatment reaction at a rotation speed of 600 rpm. After multiple washing and drying, the negatively charged zeolite-type metal sulfide composite material A1# was obtained.

[0074] (4) The photocatalytic hydrogen production performance of the obtained negatively charged zeolite-type metal sulfide composite material A1# was evaluated, and the results were as follows:

[0075] Figure 1The figure shows the X-ray powder diffraction pattern of the negatively charged zeolite-type metal sulfide 1* obtained in this example. The diffraction peaks thereof are consistent with the simulated diffraction peaks and have no impurity peaks, indicating that the synthesized material is a pure phase of the negatively charged zeolite-type metal sulfide 1*.

[0076] Figure 2 This is the X-ray powder diffraction pattern of the negatively charged zeolite-type metal sulfide composite material synthesized in this example. The diffraction peaks of the negatively charged zeolite-type metal sulfide 1* and the nanoparticle CdS appear in the spectrum at the same time, indicating the successful composite of the negatively charged zeolite-type metal sulfide 1* and the nanoparticle CdS.

[0077] Figure 3 This is a scanning electron microscope image of the negatively charged zeolite-type metal sulfide composite material 1# obtained in this example. It can be seen that the nanoparticles CdS are evenly anchored on the negatively charged zeolite-type metal sulfide 1*.

[0078] Figure 4 This is a high-resolution transmission electron microscopy image of the negatively charged zeolite-type metal sulfide composite material 1# obtained in this example. It was observed that the size of the nanoparticle CdS was about 3-5nm, and the diffraction fringes with a lattice spacing of 0.33nm corresponded to the (111) crystal plane of CdS, indicating the successful composite of the negatively charged zeolite-type metal sulfide 1* and the nanoparticle CdS.

[0079] Figure 5 , 6 The photocatalytic hydrogen production performance of the negatively charged zeolite-type metal sulfide 1* and the negatively charged zeolite-type metal sulfide composite material 1# obtained in this example shows that the prepared composite material has excellent performance. Compared with 1*, the photocatalytic hydrogen production performance of 1# is improved by two orders of magnitude.

[0080] Figure 7 , 8 The hydrogen production performance of the negatively charged zeolite-type metal sulfide composite material 1# obtained in this example after 60 hours of illumination and the X-ray powder diffraction pattern after 60 hours of illumination. During the 60 hours of illumination, the photocatalytic hydrogen production activity of 1# did not decrease significantly. In addition, the X-ray powder diffraction pattern of 1# after 60 hours of illumination did not change significantly compared with the original sample, indicating that 1# has good photocatalytic stability.

[0081] Example 2

[0082] Except for the different metal types in the metal cation exchange reaction, the method of Example 1 was followed to prepare metal cation-modified zeolite-type metal sulfides 2#, 3#, and 4#, and negatively charged zeolite-type metal sulfide composite materials A2#, A3#, and A4#.

[0083] Among them, the cation source of the metal cation-modified zeolite-type metal sulfide 2# exchange is ZnCl2;

[0084] The cation source of the exchange of metal cation-modified zeolite-type metal sulfide 3# is AgCl;

[0085] The cation source of the metal cation-modified zeolite-type metal sulfide 4# exchange is Pb(CH3CO2)2·3H2O.

[0086] Example 3

[0087] Except for the different metal cation exchange reaction methods, the method of Example 1 was followed to prepare metal cation modified zeolite-type metal sulfide 5# and negatively charged zeolite-type metal sulfide composite material A5#.

[0088] Among them, the cation exchange method of the metal cation-modified zeolite-type metal sulfide 5# was replaced by shaking instead of stirring.

[0089] Example 4

[0090] Except for the different metal cation exchange reaction times, the method of Example 1 was followed to prepare metal cation modified zeolite-type metal sulfides 6#, 7#, 8# and negatively charged zeolite-type metal sulfide composite materials A6#, A7#, A8#.

[0091] Among them, the cation exchange reaction time of metal cation-modified zeolite-type metal sulfide 6# is 12h;

[0092] The reaction time of cation exchange of metal cation-modified zeolite-type metal sulfide 7# is 24h;

[0093] The cation exchange reaction time of metal cation modified zeolite metal sulfide 8# is 48h.

[0094] Example 5

[0095] Except for the different metal cation exchange reaction temperatures, the method of Example 1 was followed to prepare metal cation modified zeolite-type metal sulfides 9#, 10#, 11# and negatively charged zeolite-type metal sulfide composite materials A9#, A10#, A11#.

[0096] Among them, the cation exchange reaction temperature of the metal cation-modified zeolite-type metal sulfide 9# is 40°C;

[0097] The cation exchange reaction temperature of the metal cation-modified zeolite-type metal sulfide 10# is 60°C;

[0098] The cation exchange reaction temperature of the metal cation modified zeolite metal sulfide 11# is 80℃.

[0099] Example 6

[0100] Except for the different post-treatment reaction times, the method of Example 1 was followed to prepare metal cation-modified zeolite-type metal sulfides, and post-treatment was performed to obtain negatively charged zeolite-type metal sulfide composite materials A12#, A13#, and A14#.

[0101] Among them, the post-treatment reaction time of negatively charged zeolite-type metal sulfide composite material A12# is 4h;

[0102] The post-treatment reaction time of negatively charged zeolite-type metal sulfide composite material A13# is 8h;

[0103] The post-treatment reaction time of the negatively charged zeolite-type metal sulfide composite material A14# is 12h.

[0104] Example 7

[0105] Except for the different post-treatment reaction temperatures, the method of Example 1 was followed to prepare metal cation-modified zeolite-type metal sulfides, and post-treatment was performed to obtain negatively charged zeolite-type metal sulfide composite materials A15#, A16#, and A17#.

[0106] Among them, the post-treatment reaction temperature of negatively charged zeolite-type metal sulfide composite material A15# is 40°C;

[0107] The post-treatment reaction time of negatively charged zeolite-type metal sulfide composite material A16# is 60°C;

[0108] The post-treatment reaction time of the negatively charged zeolite-type metal sulfide composite material A17# is 80°C.

[0109] Example 8

[0110] Except for the post-treatment reaction type, the method of Example 1 was followed to prepare metal cation-modified zeolite-type metal sulfides, and post-treatment was performed to obtain negatively charged zeolite-type metal sulfide composite materials A18#, A19#, A20#, and A21#.

[0111] Among them, the negatively charged zeolite-type metal sulfide composite material A18# was treated with sodium chloride;

[0112] The electronegative zeolite-type metal sulfide composite material A19# was treated with sodium bromide;

[0113] The negatively charged zeolite-type metal sulfide composite material A20# was treated with potassium iodide;

[0114] The electronegative zeolite-type metal sulfide composite material A21# was treated with sodium hypophosphite.

[0115] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a negatively charged zeolite-type metal sulfide composite material, characterized in that: The steps include: S1, placing a mixture containing a metal salt, sulfur powder, a cation source, and water in a closed container for hydrothermal reaction to obtain a negatively charged zeolite-type metal sulfide precursor; S2, mixing a negatively charged zeolite-type metal sulfide precursor and a metal cation source in a solvent to perform a metal cation exchange reaction to obtain a metal cation-modified negatively charged zeolite-type metal sulfide; S3, post-treating the negatively charged zeolite-type metal sulfide modified with metal cations and a post-treating agent in a solvent to obtain the negatively charged zeolite-type metal sulfide composite material.

2. The preparation method according to claim 1, characterized in that: In step S1, when the metal salt is one, the metal element is selected from one of In, Ga and Ge; Preferably, when there are two metal salts, the metal element is selected from one of the combinations of In / M (M = Zn, Cd, Fe, Co, Mn, Ge, Sn, Cu), Ga / Ge, Ga / Sn, Ge / Zn, Ge / Cu, Ge / Mn, Sn / Zn, and Sn / Cd; Preferably, when there are three kinds of metal salts, the metal element is selected from one of the combinations of Ge / Cd / Zn, Ge / Ga / Zn, Ge / Sn / Zn, Zn / Ga / Ge, Cu / Ga / Sn, Cu / In / Sn, Mn / Ga / Sn, and Mn / Zn / In; Preferably, in step S1, the cation source in the cation source is selected from at least one of cesium salts, rubidium salts, strontium salts, potassium salts, sodium salts, amine salts, methylamine, dimethylamine, tris(2-aminoethyl)amine, N-aminoethylpiperazine, N-(2-aminoethyl)morpholine, and 1-butyl-3-methylimidazole; Preferably, in step S1, the molar ratio of the metal salt to the sulfur powder and the cation source is 1:(1-5):(5-20) in terms of element molar amount; Preferably, in step S1, the ratio of the cation source to water is 1 mmol: 1 to 30 mL; Preferably, in step S1, the conditions of the hydrothermal reaction include: a reaction temperature of 100 to 220° C., a reaction time of 24 to 240 h, and natural cooling after the reaction is completed.

3. The preparation method according to claim 1, characterized in that: In step S2, the cation in the metal cation source is selected from Cd 2+ 、Zn 2+ , Pb 2+ 、Mo 4+ , Cu 2+ 、Bi 3+ 、Ag + 、Co 2+ 、Ni 2+ , Fe 2+ At least one of; The metal cation source is selected from one of acetate metal salts, nitrate metal salts, oxalate metal salts, chloride metal salts, and carbonate metal salts; Preferably, the solvent in step S2 is one of water, ethanol and N-methylpyrrolidone; Preferably, in step S2, the cation concentration in the metal cation source is 0.05 to 0.5 mol / L; Preferably, in step S2, the weight ratio of the negatively charged zeolite-type metal sulfide precursor to the metal cation source is 1:0.5-3; Preferably, in step S2, the ratio of the negatively charged zeolite-type metal sulfide precursor to the solvent is 1 mg: 0.005-0.1 mL; Preferably, the weight ratio of the negatively charged zeolite-type metal sulfide precursor to the post-treatment agent in step S3 is 1:1 to 10; Preferably, the ratio of the negatively charged zeolite-type metal sulfide precursor to the solvent in step S3 is 1 mg: 0.005-0.1 mL.

4. The preparation method according to claim 1, characterized in that: In step S2, the conditions for the metal cation exchange reaction include: being carried out under at least one of stirring and shaking, the reaction temperature is 20 to 120° C., and the reaction time is 12 to 72 hours; Preferably, in step S2, the stirring and / or shaking speed is 200-1000 rpm.

5. The preparation method according to claim 1, characterized in that: In step S3, the post-treatment reaction is selected from one of a sulfurization reaction, a halogenation reaction, and a phosphating reaction; Preferably, the solvent in step S3 is one of water, ethanol and N-methylpyrrolidone.

6. The preparation method according to claim 5, characterized in that: When the post-treatment reaction is a sulfurization reaction, the cation in the metal cation source is selected from Cd 2+ 、Zn 2+ , Pb 2+ 、Mo 4+ , Cu 2+ 、Bi 3+ One of the above, the post-treatment agent is a sulfur source; Preferably, the sulfur source is selected from at least one of sodium sulfide, thiourea and thioacetamide; Preferably, the conditions for the vulcanization reaction include: reacting under at least one of stirring, shaking, and hydrothermal conditions, and the vulcanization reaction time is 6 to 24 hours; Preferably, when the vulcanization reaction is carried out under stirring and / or shaking conditions, the temperature of the vulcanization reaction is 20 to 100° C., and the stirring and / or shaking speed is 200 to 1000 rpm; Preferably, when the vulcanization reaction is carried out under hydrothermal conditions, the temperature of the vulcanization reaction is 100-200°C.

7. The preparation method according to claim 5, characterized in that: When the post-treatment reaction is a halogenation reaction, the cation in the metal cation source is selected from Ag. + , the post-treatment agent is a halogen source; Preferably, the halogen source is selected from at least one of potassium halide and sodium halide; Preferably, the halogen in the halogen source is selected from at least one of chlorine, bromine and iodine; Preferably, the halogenation reaction conditions include: dark stirring and / or dark shaking at a speed of 200 to 1000 rpm, the halogenation reaction temperature is 20 to 40° C., and the halogenation reaction time is 0.5 to 6 h.

8. The preparation method according to claim 5, characterized in that: When the post-treatment reaction is a phosphating reaction, the cation in the metal cation source is selected from Co 2+ 、Ni 2+ , Fe 2+ One of the above, the post-treatment agent is a phosphorus source; Preferably, the phosphorus source is selected from at least one of phosphine and sodium hypophosphite; Preferably, the conditions of the phosphating reaction include: carrying out the reaction in an inert atmosphere, the phosphating reaction temperature is 300-600° C., and the phosphating reaction time is 2-6 hours.

9. The negatively charged zeolite-type metal sulfide composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The negatively charged zeolite-type metal sulfide composite material comprises a host material and guest nanoparticles; The main material is an electronegative zeolite-type metal sulfide; The guest nanoparticles are selected from at least one of sulfides, halides, and phosphides of cations in the metal cation source; The guest nanoparticles are anchored to the host material.

10. Use of the negatively charged zeolite-type metal sulfide composite material prepared by the preparation method according to any one of claims 1 to 8 or the negatively charged zeolite-type metal sulfide composite material according to claim 9 as a catalyst in photocatalytic hydrogen production.